Behavioral intelligence in plant breeding: A framework for qualitative research - Cavicchioli, Martina; Kramer, Berber; Trachtman, Carly (International Food Policy Research Institute, 2023)
This issue brief introduces a conceptual framework to describe the factors that inform farmers’ varietal uptake choices, by integrating choice behavior alongside more contextual and technical aspects of seed uptake. The framework was developed to support qualitative data analysis for generating behavioral intelligence about farmers’ decision-making about crop varieties, which may be of use to government agencies, nongovernmental organizations, and companies that operate in the seed sector.